Framing Analysis of Online Media on Air Pollution in Jakarta Between Detik.com and Liputan 6.com - Bastian, Irsa; Ow Mun Waei; Ria Restina Robiyanyi; Metta Fitri Wulanjana Putri (International Journal of Environmental Communication (ENVICOMM), 2023)
Air pollution in Jakarta has emerged as a critical environmental issue. This study employs a qualitative descriptive approach to analyze how Detik.com and Liputan 6.com, prominent online media platforms, frame the issue of air pollution in Jakarta. Utilizing Robert N. Entman's framing analysis, we explore the news narratives and perspectives presented by these media outlets. The comparative study aims to reveal distinct framing strategies and their implications for public understanding and policy discourse on Jakarta's air quality. Using a qualitative descriptive approach, we analyzed two online media outlets reporting on this issue. We employed Robert N. Entman's framing analysis to understand how online media frame news related to air pollution in Jakarta. This analysis was conducted to identify patterns in news, narratives, and opinions related to air pollution and its causes. Through a comparative study, the variables analyzed included media framing as variable X and the issue of air pollution as variable Y. By considering these variables, the analysis provides a deeper understanding of Jakarta's air pollution problem. This research compares the reporting approaches of the online media platforms Detik and Liputan6, discussing the environmental air pollution issue in Jakarta with the aim of producing relevant comparative data. The results of this analysis are expected to provide deeper insights into how online media construct and present information about air pollution. The understanding gained from the comparison between Detik and Liputan6 is hoped to raise public awareness and motivate more effective measures to tackle the air pollution problem in Jakarta.